Practical design considerations for secondary air injection in wood-burning cookstoves: An experimental study. (2020) - Caubel, Julien J.; Rapp, Vi H.; Chen, Sharon S.; Gadgil, Ashok J.
Abstract: Billions of households worldwide cook using biomass fires and suffer from the toxic smoke emitted into their homes. Laboratory studies of wood-burning cookstoves demonstrate that secondary air injection can greatly reduce the emission of harmful air pollution, but these experimental advancements are not easily translated into practical cookstove designs that can be widely adopted. In this study, we use a modular cookstove platform to experimentally quantify the practical secondary air injection design requirements (e.g., flow rate, pressure, and temperature) to reduce mass emissions of particulate matter (PM), carbon monoxide (CO), and black carbon (BC) by at least 90% relative to a traditional cooking fire. Over the course of 111 experimental trials, we illuminate the physical mechanisms that drive emission reductions, and outline fundamental design principles to optimize cookstove performance. Using the experimental data, we demonstrate that low-cost (<10) fans and blowers are available to drive the secondary flow, and can be independently powered using an inexpensive thermoelectric generator mounted nearby. Furthermore, size-resolved PM measurements show that secondary air injection inhibits particle growth, but the total number of particles generated remains relatively unaffected. We discuss the potential impacts for human health and investigate methods to mitigate the PM formation mechanisms that persist.